Organization of business games as an interactive method of teaching foreign languages to students of hei aquiring specialties connected with the transport industry - Makoviei, O. M.; Маковєй, О. М.; Маковей, О. Н. (Харьковский национальный автомобильно-дорожный университет, 2018)
In order to train highly skilled specialists, lectures, seminars, laboratories and practical classes, as well as other forms of training, including the business game as an interactive method of teaching foreign languages to students are held. It is noted that when presenting the studying material in a game form, students are active and interested in the results of their educational activities. There is an urgent need for a serious rethink of our representations. Goal. The goal of the given article is to determine the specifics of business games and the possibility of their appli-cation in the educational process of HEI in order to intensify the study of foreign languages by students of specialties connected with the transport industry. Methodology. The specificity of the methodological support of the business game, the content and purpose of the game in teaching a foreign language are investigated. It is noted that a business game can help achieve both the educational and developmental goals of the collective activity of students in the process of teaching a foreign language. Results. The factors and the professionally oriented character of the students’ specialty for the preparation and conduct of the business game are determined. The essence, specificity and the methodological support of the business game as an important form of training students of transport specialties to provide foreign language communication in higher educational institutions are considered. Originality. The author proposed recommenda-tions for the development and use of business games. Practical value. Interactive teaching methods help to develop skills of professional communication in a foreign language, promote the development of necessary interpersonal communicative qualities. Optimal introduction of role and business games in the educational and extracurricular process is an important and necessary factor in attracting students to independent active acquisition of knowledge, skills and abilities, development of their cognitive activity, formation of the creative personality of students of higher technical educational institutions.
Організація ділової гри як інтерактивного методу навчання іноземної мови студентів транспортних спеціальностей ВНЗ
Организация деловой игры как интерактивного метода обучения иностранному языку студентов транспортных специальностей ВУЗов
Keywords: modern teaching methods; business game; functions of business game; methodical provision of business games; organization of business game; interpersonal communicative qualities; forms of training; foreign language communication; cognitive activity; сучасні методи навчання; ділова гра; функції ділової гри; методичне забезпечення ділових ігор; організація ділової гри; современные методы обучения; деловая игра; элементы деловой игры; методологическое обеспечение деловых игр; организация деловой игры; 378.147:004